Examining the Status of English as a Medium of Instruction in Sub-Saharan Africa: A Comparative Study of Botswana and Nigeria - Tom-Lawyer, Oris; Thomas, Michael; Kalane, Maureen Sindisiwe (European Scientific Journal, ESJ, 2021)
This paper examines the status of English as a medium of instruction in Sub-Saharan Africa (SSA) by comparing how it is taught and learned in Botswana and Nigeria. The paper’s argument is based on the premise that learners acquire literacy skills in a familiar language (Williams, 2011). The English language is an official language in the two countries and has been linked to their social, economic and political development (Cholakova, 2015). The aim of the study is to compare the status of English as a medium of instruction in Botswana and Nigeria, identify and examine the implications for its use, and recommend best practice for policymakers in the field. Based on a systematic review of research between 2000 and 2021, the paper identifies several key findings affecting both countries: the insufficient acquisition of literacy skills in English, the need for a language policy review in Botswana, and the need for a thorough review of teacher quality by the governments of both countries if United Nations Sustainable Development Goal (SDG) 4.c is to be achieved by the deadline of 2030. The implications of the review for both countries are that pupils drop out of school as a result of their lack of understanding of English; a non-credit pass in English at the secondary level can hinder students’ career progression; English remains parents’ educationally preferred language; and policy makers need to have a strategic awareness of how English and other languages are used in their communities for educational purposes.